IMPLEMENTASI MEDIKOLEGAL TRANSPLANTASI ORGAN DARI DONOR JENAZAH UNTUK PENINGKATAN KESEHATAN MASYARAKAT - M. Faizal Zulkarnaen (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Human organ transplantation is one alternative therapies that has been growing fastly. Imbalance between organ requirement and availability cause organ shortage organ, that can be solved by using cadaveric donor. The problem formulations are “How is the medico legal implementation of organ transplantation from cadaveric donor to increase the public health?” and “What are the obstacles and solutions for the medico legal implementation of organ transplantation from cadaveric donor to increase the public health?”. The research method are normative juridical and empiric approach by means of thinking deductive and specification of the descriptive analytical research, qualitative normative and empiric as analysis method towards primary and secondary data. Research reveals that medico legal implementation of organ transplantation from cadaver organ in Indonesia is very poor, limited only to cornea; obstacles arise from medic aspect where hospital facing shortage of competent human resources and facilities, less socialization from doctors, public unawareness about advantages and social paradigm where a dead body should be buried whole; law aspect where the law is still unclear. Therefore doctors should be trained, facilities supply for hospitals and wide socialization. Public also has to change their mind set. Transplantation regulation should be replaced in accordance with the new ratified Health Law.